PENINGKATAN KEMAMPUAN MEMAHAMI TEKS TANTANGAN MENGGUNAKAN METODE PEMBELAJARAN STAD SISWA KELAS IX SMPN 1 KARANGPLOSO - Diah Erna Triningsih (Center of Language and Cultural Studies, 2018)
This study aims to see the improvement to understand challenge text of the ninth graders of SMPN 1 Karangploso using STAD of cooperative learning method. This study used classroom action research assigning 31 students consisting of 14 male and 17 female students. This research implemented two cycles each of which applied planning, implementing, observing and reflection. The results showed that the ability to understand the text of the challenge increased in cycle 1. Distribution of students accomplishment are 10 (33.33%) low, 15 (48.39%) moderate, and 6 (19.35%) high. In cycle 2, students accomplishment are satisfied as no low scores are achieved. Middle scores are gained by 17 (54,83%) having a score range of 78-84, and 14 (45.16%) achieved very good score ranging from 85-100. Attainment of students activities during the class has also increased from 65% to 82% showing that STAD method evidently improves students attainment on challenge text.